Effects of sodium bicarbonate on 200 m time trial performance and physiological responses in swimmers: a systematic review and meta-analysis of randomized controlled trials - Huang, D.; Wang, X.; Takagi, H.; Wang, Z.; Wang, C.; Yang, L.; Huang, B. (Research in Sports Medicine, 2025)
This systematic review and meta-analysis evaluated the effects of sodium bicarbonate (NaHCO3) supplementation on 200 m time trial performance and physiological responses in swimmers, following PRISMA guidelines. A comprehensive search across five databases identified eligible randomized controlled trials comparing NaHCO3 with placebo. Outcomes were 200 m time, blood bicarbonate, blood lactate, and blood pH. Results showed significant increases in blood bicarbonate (SMD = 1.09, 95% CI = 0.38 to 1.79, P<0.01), blood lactate (SMD = 0.76, 95% CI = 0.24 to 1.29, P<0.01) and blood pH (SMD = 1.02, 95% CI = 0.33 to 1.71, P<0.01), but no effect on 200 m time (SMD = 0.26, 95% CI -0.58 to 1.10). These findings suggest NaHCO3 enhances certain physiological responses but does not improve 200 m performance, though data limitations require cautious interpretation.